Prevalence and Levels of Depression, Anxiety, and Stress among Pregnant Women during the COVID-19 Pandemic in Bangladesh - Sara Khan; Mohammad , Nurunnabi; Imtiaz Habib; Sayeda Mukta Chowdhury; Nazem Al Qureshee Rafat; Farzana Akter; Naznin Akter Nizum; Saima Bibi; Mohammad Delwer Hossain Hawlader (Bangladesh Journal of Infectious Diseases, 2025)
Background: COVID-19 infection has had an extensive effect on people's lives around the world, and pregnancy causes significant immune suppression, making women more vulnerable, particularly in low- and middle-income countries. Objective: The purpose of the present study was to assess the prevalence and levels of depression, anxiety, and stress (DAS) among pregnant women during the COVID-19 pandemic. Methodology: This cross-sectional study was conducted to assess the prevalence and levels of depression, anxiety, and stress (DAS) among conveniently selected 150 pregnant women during the COVID-19 pandemic. The Depression, Anxiety, and Stress Scale-21 (DASS-21) scale was used to construct this semi-structured questionnaire for data collection during the study period. Results: Pregnant women stipulated a high rate of depression (86.7%), anxiety (78.0%), and stress (75.3%). The majority of them reported moderate stress (48.0%), extreme severe anxiety (29.3%), and moderate sadness (36.0%). Stress was higher among those who completed secondary education, worked in the private sector, had a nuclear family, had a lower household income, had a history of planned contraception, no history of normal or caesarean section or abortion, and had irregular ANC. Anxiety was higher in the 18 to 19 year old age group, private service holder, nuclear family, urban setting, low household income, primigravida, no history of planned contraception, no history of caesarean section or abortion, history of normal birth, and early gestation. Depression was higher in the age group 20 to 29 years, completed primary education, private service holder, nuclear family, and less household’s income. Conclusion: This study reveals that higher prevalence of depression, anxiety and stress among pregnant women. To improve the quality of life, factors such as depression, anxiety, and stress should be addressed. Bangladesh Journal of Infectious Diseases, June 2025;12(1):99-107